2000
DOI: 10.1136/ard.59.1.39
|View full text |Cite
|
Sign up to set email alerts
|

Macrovascular disease and systemic sclerosis

Abstract: Objective-To determine if macrovascular disease is more prevalent in systemic sclerosis (SSc) compared with unaVected subjects. Methods-54 patients with SSc (both limited and diVuse disease) and 43 unaVected control subjects of similar age and sex were recruited. All subjects underwent a basic screen for conventional atherosclerotic disease risk factors. All had noninvasive vascular assessments-that is, carotid duplex scanning and measurement of ankle brachial blood pressure index-to identify the presence of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
77
0
25

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 154 publications
(111 citation statements)
references
References 27 publications
9
77
0
25
Order By: Relevance
“…The same has also been reported by Bartoli et al [17], kaloudi et al [25] and Muro et al [34]. However studies by Ho et al [35] and Wan et al [20] had contradictory results. Furthermore, our study revealed a statistically significant inverse correlation with age and duration of disease.…”
Section: Discussionsupporting
confidence: 53%
“…The same has also been reported by Bartoli et al [17], kaloudi et al [25] and Muro et al [34]. However studies by Ho et al [35] and Wan et al [20] had contradictory results. Furthermore, our study revealed a statistically significant inverse correlation with age and duration of disease.…”
Section: Discussionsupporting
confidence: 53%
“…Wan et al 10 e Ho et al 26 também não encontraram associação de DMV com as formas clínicas limitada e difusa, que apresentaram a mesma prevalência.…”
Section: Discussionunclassified
“…Esse índice também pode ser usado como um bom indicador de DAP em pacientes com ES 10,26,41 . Divide-se a pres-maior pressão sistólica no tornozelo dividida pela maior pressão sistólica braquial.…”
Section: Métodos Diagnósticos Da Dmvunclassified
See 1 more Smart Citation
“…Tradicionalmente, o envolvimento vascular na ES tem sido considerado como predominantemente microvascular, associado a um desbalanço entre a vasoconstrição e a vasodilatação, em favor da vasoconstrição (2,5) . Nos últimos anos, a presença de acometimento macrovascular tem sido observada de maneira crescente na ES (6)(7)(8)(9) . …”
unclassified